Repeat treatment with rifaximin improves irritable bowel syndrome-related quality of life: a secondary analysis of a randomized, double-blind, placebo-controlled trial. (September 2017) - Cash, Brooks D.; Pimentel, Mark; Rao, Satish S. C.; Weinstock, Leonard; Chang, Lin; Heimanson, Zeev; Lembo, Anthony
Background: Diarrhea-predominant irritable bowel syndrome (IBS-D) impairs patient quality of life (QOL). Rifaximin is an oral, nonsystemic antibiotic indicated for IBS-D. The objective of this secondary analysis was to evaluate rifaximin retreatment on IBS-related QOL in patients with IBS-D. Methods: Patients received open-label rifaximin 550 mg three times daily for 2 weeks. Clinical responders [simultaneously meeting weekly response criteria for abdominal pain (⩾30% improvement from baseline in mean weekly pain score) and stool consistency (⩾50% decrease from baseline in number of days/week with Bristol Stool Scale (BSS) type 6 or 7 stools) during ⩾2 of first 4 weeks posttreatment] who relapsed during an up to 18-week treatment-free observation phase were randomly assigned to receive two 2-week courses of double-blind rifaximin or placebo, separated by 10 weeks. A validated 34-item IBS-QOL questionnaire examined patient responses in 8 domains. Results: The 2579 patients receiving open-label rifaximin experienced a mean improvement from baseline in IBS-QOL overall score of 54.9%. Responders to open-label rifaximin ( n = 1074 of 2438 evaluable; 44.1%) had significantly greater improvement from baseline in IBS-QOL overall and all eight subdomain scores, including dysphoria, food avoidance, interference with activity, body image, and sexual function versus nonresponders at 4 weeks posttreatment ( n = 1364; p < 0.001 for all comparisons). A significantly greater percentage of responders to open-label rifaximin achieved the minimally clinically important difference (MCID; ⩾14-point improvement from baseline) in the overall IBS-QOL score versus nonresponders [ n = 561 (52.2%) versus n = 287 (21.0%); p < 0.0001]. Among 636 patients with IBS-D relapse, the MCID in the overall IBS-QOL score was achieved by a significantly greater percentage of patients receiving double-blind rifaximin versus placebo (38.6% versus 29.6%, respectively; p = 0.009). Conclusions: Open-label and blinded retreatment with a short course (2 weeks) of rifaximin improved IBS-QOL in patients with IBS-D [ClinicalTrials.gov identifier: NCT01543178].